3D SERS Imaging Using Chemically Synthesized Highly Symmetric Nanoporous Silver Microparticles. Issue 29 (30th May 2016) - Vantasin, Sanpon; Ji, Wei; Tanaka, Yoshito; Kitahama, Yasutaka; Wang, Mengfan; Wongravee, Kanet; Gatemala, Harnchana; Ekgasit, Sanong; Ozaki, Yukihiro
Abstract: 3D surface‐enhanced Raman scattering (SERS) imaging with highly symmetric 3D silver microparticles as a SERS substrate was developed. Although the synthesis method is purely chemical and does not involve lithography, the synthesized nanoporous silver microparticles possess a regular hexapod shape and octahedral symmetry. By using p ‐aminothiophenol (PATP) as a probe molecule, the 3D enhancement patterns of the particles were shown to be very regular and predictable, resembling the particle shape and exhibiting symmetry. An application to the detection of 3D inhomogeneity in a polymer blend, which relies on the predictable enhancement pattern of the substrate, is presented. 3D SERS imaging using the substrate also provides an improvement in spatial resolution along the Z axis, which is a challenge for Raman measurement in polymers, especially layered polymeric systems. Abstract : Yes SERS : 3D surface‐enhanced Raman scattering (SERS) imaging using highly symmetric chemically synthesized 3D silver microparticles as a SERS substrate was developed. The 3D enhancement patterns of the particles were shown to be very regular and predictable, resembling the particle shape and exhibiting symmetry. This system was applied to the detection of 3D inhomogeneity in a polymer blend, which relies on the predictable enhancement pattern of the substrate.